Welfare Index of Person with Disabilities in Indonesia, 2018 - Ni Putu Ayu Chyntia Manikka Sari; Tiodora Hadumaon Siagian (Proceedings of The International Conference on Data Science and Official Statistics, 2021)
Most people with disabilities in Indonesia still live in vulnerable, backward, or poor conditions due to restrictions, obstacles, difficulties, and reduction or elimination of the rights of persons with disabilities. In realizing prosperity for all Indonesian people, it should be fair and not contain discriminatory elements, including persons with disabilities. For this reason, a measure of the achievement of the welfare of persons with disabilities is needed as evaluation support material in making plans and policies. This study aims to obtain the welfare factors of persons with disabilities and compile them into the Welfare Index of Persons with Disabilities (WIPD). The construction of the WIPD was carried out using the exploratory factor analysis method. Based on the results, 20 indicators formed five factors, namely accessibility, housing and access to information, physical and spiritual well-being, social relations and sanitation, and economic well-being. From the WIPD scores, it is known that there is a gap in WIPD achievement between the Western and the Eastern Region of Indonesia. For this reason, the government needs to prioritize inclusive development in provinces with very low and low WIPD achievements.